Recycled concrete with high heat-conducting property and preparation method thereof

By using thermal conductivity agent-Eloshi nanotube composite materials and modified polyacrylonitrile-based carbon fibers in concrete, the thermal conductivity network is constructed, and the problem of insufficient thermal conductivity of traditional concrete is solved, and the improvement of high thermal conductivity and mechanical properties is achieved. In various application scenarios.

CN119263713APending Publication Date: 2025-01-07DANGYANG ZHONGYANG BUILDING MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411401862.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional concrete has poor thermal conductivity and cannot meet the needs of high thermal conductivity in some special scenarios, such as factory buildings with good heat dissipation and concrete pavement that melts snow.

Method used

Using thermal conductivity agent-Elostone nanotube composite material and modified polyacrylonitrile-based carbon fiber, the thermal conductivity network and three-dimensional thermal conductivity network are constructed through the tubular structure of Elostone nanotubes, which enhances the thermal conductivity of concrete, and uses hydrochloric acid etching and ultrasound. High-efficiency thermal conductivity carriers are prepared by dispersing and other methods, and combined with the use of modified polyacrylonitrile-based carbon fibers, the mechanical properties and durability of concrete are improved.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of concrete, ensures the stable performance of thermal conductivity throughout the life cycle of concrete, and is suitable for industrial production and widening application scenarios of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075496170000061
    Figure BDA0005075496170000061
  • Figure BDA0005075496170000071
    Figure BDA0005075496170000071
  • Figure BDA0005075496170000081
    Figure BDA0005075496170000081
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses recycled concrete with high heat-conducting property and a preparation method thereof. The invention discloses recycled concrete with high heat-conducting property. The recycled concrete is prepared from the following raw materials in parts by weight: cement, mineral powder, fly ash, coarse aggregate, fine aggregate, a heat-conducting agent-halloysite nanotube composite material, modified polyacrylonitrile-based carbon fiber, water and an additive. The preparation method comprises the following steps: S1, mixing and stirring the cement, the mineral powder, the fly ash, the coarse aggregate and the fine aggregate; s2, adding a heat conduction agent-halloysite nanotube composite material, modified polyacrylonitrile-based carbon fibers and 50% of water, and mixing and stirring; and S3, adding the additive and the residual water, and mixing and stirring to prepare the recycled concrete with high heat-conducting property. The recycled concrete with high heat-conducting property prepared by the invention has relatively high breaking strength and compressive strength and good heat-conducting property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of concrete, and in particular to a recycled concrete with high thermal conductivity and a preparation method thereof. Background Art

[0002] Recycled concrete refers to new concrete made by crushing, cleaning, and grading discarded concrete blocks, mixing them with grading in a certain proportion, partially or completely replacing natural aggregates such as sand and gravel (mainly coarse aggregates), and then adding cement, water, etc.

[0003] Traditional concrete is widely used in various civil engineering projects due to its high compressive strength, good durability, and wide range of strength grades. However, the thermal conductivity of traditional concrete is usually between 1.4-1.7W / (m·K), and its thermal conductivity is not very strong. However, there are scenarios in life where concrete with high thermal conductivity is needed, such as factory buildings that require good heat dissipation, and when using heat conduction to melt snow on concrete pavements. Therefore, there is an urgent need for concrete with high thermal conductivity. Summary of the invention

[0004] In order to solve at least one of the above technical problems, a green recycled concrete with high thermal conductivity is developed to meet the demand for high thermal conductivity building materials in the construction field and expand the use scenarios of concrete. The present application provides a recycled concrete with high thermal conductivity and a preparation method thereof.

[0005] On the one hand, the present application provides a recycled concrete with high thermal conductivity, comprising the following raw materials in parts by weight: 120-150 parts of cement, 15-30 parts of mineral powder, 20-30 parts of fly ash, 150-210 parts of coarse aggregate, 320-400 parts of fine aggregate, 10-18 parts of thermal conductor-halloysite nanotube composite material, 5-9 parts of modified polyacrylonitrile-based carbon fiber, 40-55 parts of water, and 5-10 parts of admixture.

[0006] By adopting the above technical scheme, the present application uses a thermal conductor-halloysite nanotube composite material, and uses halloysite nanotubes to load thermal conductors. The halloysite nanotubes have a tubular structure and can form a continuous heat conduction path, so as to build a heat conduction network in concrete. After the halloysite nanotubes load the thermal conductor, the presence of the thermal conductor can further enhance the effect of this heat conduction network. The tubular structure of the halloysite nanotubes can also protect the loaded thermal conductor to prevent it from agglomerating or degrading in concrete, and can ensure that the thermal conductor maintains stable thermal conductivity throughout the life cycle of the concrete. At the same time, there is a good interface interaction between the halloysite nanotubes and the concrete matrix, which can enhance the bonding force between the nanotubes and the matrix. This enhanced interface interaction can not only improve the thermal conductivity, but also improve the mechanical properties and durability of the concrete. Modified polyacrylonitrile-based carbon fiber has good dispersibility in concrete, can avoid agglomeration, has high axial thermal conductivity, can form a three-dimensional heat conduction network in the concrete, and significantly improve the thermal conductivity of the concrete. Polyacrylonitrile-based carbon fiber can also improve the tensile strength and toughness of concrete.

[0007] Optionally, the preparation method of the thermal conductor-halloysite nanotube composite material comprises the following steps: A1, adding the halloysite nanotubes to a 3 mol / L hydrochloric acid solution, heating and stirring in a water bath for 6-8 hours, centrifuging to separate the solid matter, and washing and grinding the solid matter to obtain the halloysite nanotubes after hydrochloric acid etching; A2, mixing the hydrochloric acid-etched halloysite nanotubes obtained in step A1, a thermal conductor and water, and ultrasonically dispersing them in an ice bath for 40-60 minutes, and then vacuum drying the obtained suspension; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24-30 hours, and grind into powder to obtain the thermal conductor-halloysite nanotube composite material.

[0008] By adopting the above technical solution, the halloysite nanotubes after hydrochloric acid etching can provide more thermal conductor attachment sites and load as much thermal conductor as possible.

[0009] Optionally, in step A2, the weight ratio of the halloysite nanotubes, the thermal conductor and water after hydrochloric acid etching is 1:(9-13):(80-100).

[0010] Optionally, the preparation method of the modified polyacrylonitrile-based carbon fiber includes the following steps: dissolving dopamine hydrochloride in a Tris aqueous solution, adding the polyacrylonitrile-based carbon fiber and soaking for 10-12 hours, washing, and freeze-drying to obtain the modified polyacrylonitrile-based carbon fiber; the dosage ratio of dopamine hydrochloride and Tris aqueous solution is (4-6) mg:1 mL.

[0011] Optionally, the weight ratio of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is (1.6-2.4):1.

[0012] Optionally, the sum of the weights of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber accounts for 2.2-3.3% of the total weight of the raw materials of the recycled concrete with high thermal conductivity.

[0013] By adopting the above technical scheme, the present application further limits the weight ratio of the thermal conductor-halloysite nanotube composite material and the polydopamine-modified polyacrylonitrile-based carbon fiber, as well as the weight of the two and their proportion in the total weight of concrete, thereby controlling costs while ensuring that the recycled concrete with high thermal conductivity has the best thermal conductivity, working performance, strength and durability.

[0014] Optionally, the coarse aggregate consists of natural coarse aggregate and recycled coarse aggregate in a weight ratio of (2.5-4):1.

[0015] By adopting the above technical solution, excessive addition of recycled coarse aggregate will lead to a decrease in concrete strength. This application limits the weight ratio of natural coarse aggregate and recycled coarse aggregate in the coarse aggregate, thereby ensuring the strength of concrete and recycling waste concrete blocks as much as possible.

[0016] Optionally, the admixture includes a polycarboxylic acid high-efficiency water reducer, an air entraining agent and a dispersant in a weight ratio of (4-6):(2-3):(2-3).

[0017] In a second aspect, the present application provides a method for preparing the above-mentioned recycled concrete with high thermal conductivity, comprising the following steps: S1, mixing cement, mineral powder, fly ash, coarse aggregate and fine aggregate at 300-350 rpm for 10-15 min; S2, adding the thermal conductor-halloysite nanotube composite material, modified polyacrylonitrile-based carbon fiber and 50% of water, and mixing and stirring at 300-350 rpm for 5-8 minutes; S3. Add the admixture and the remaining water, mix and stir at 400-450 rpm for 10-15 minutes to obtain the recycled concrete with high thermal conductivity.

[0018] By adopting the above technical solution, the method for preparing recycled concrete with high thermal conductivity provided by the present application can achieve uniform mixing and effective dispersion of raw materials. At the same time, the method is simple to operate, highly controllable, suitable for industrial production, and has broad application prospects.

[0019] In summary, the present invention includes at least one of the following beneficial technical effects: 1. This application uses a thermal conductor-halloysite nanotube composite material, and uses halloysite nanotubes to load thermal conductors. The halloysite nanotubes have a tubular structure and can form a continuous heat conduction path, thereby constructing a heat conduction network in concrete. After the halloysite nanotubes are loaded with thermal conductors, the presence of the thermal conductor can further enhance the effect of this heat conduction network. The tubular structure of the halloysite nanotubes can also protect the loaded thermal conductor to prevent it from agglomerating or degrading in concrete, and can ensure that the thermal conductor maintains stable thermal conductivity throughout the life cycle of the concrete. At the same time, there is a good interface interaction between the halloysite nanotubes and the concrete matrix, which can enhance the bonding force between the nanotubes and the matrix. This enhanced interface interaction can not only improve the thermal conductivity, but also improve the mechanical properties and durability of the concrete. Modified polyacrylonitrile-based carbon fiber has good dispersibility in concrete, can avoid agglomeration, has high axial thermal conductivity, can form a three-dimensional thermal conduction network in concrete, and significantly improve the thermal conductivity of concrete. Polyacrylonitrile-based carbon fiber can also improve the tensile strength and toughness of concrete.

[0020] 2. The method for preparing recycled concrete with high thermal conductivity provided in this application can achieve uniform mixing and effective dispersion of raw materials. At the same time, the method is simple to operate, highly controllable, suitable for industrial production, and has broad application prospects. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments. Specific embodiments

[0022] Preparation Example 1 Preparation Example 1 This preparation example provides a modified polyacrylonitrile-based carbon fiber, and the preparation method includes the following steps: dissolving dopamine hydrochloride in a Tris aqueous solution, then adding the polyacrylonitrile-based carbon fiber and soaking it for 11 hours, washing, and freeze-drying to obtain the modified polyacrylonitrile-based carbon fiber; the dosage ratio of dopamine hydrochloride and Tris aqueous solution is (4-6) mg:1 mL.

[0023] Preparation Example 2-4 Preparation Example 2 This preparation example provides a thermal conductor-halloysite nanotube composite material, and the preparation method includes the following steps: A1, adding the halloysite nanotubes to a 3 mol / L hydrochloric acid solution, heating and stirring for 8 h in a water bath, centrifuging to separate the solid matter, and washing and grinding the solid matter to obtain the halloysite nanotubes after hydrochloric acid etching; A2, mixing the hydrochloric acid-etched halloysite nanotubes obtained in step A1, a thermal conductor and water, and performing ultrasonic dispersion for 60 minutes in an ice bath, and then vacuum drying the obtained suspension; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24 hours, and grind into powder to obtain the thermal conductor-halloysite nanotube composite material.

[0024] In step A2, the weight ratio of the halloysite nanotubes, the thermal conductor and the water after the hydrochloric acid etching is 1:9:80; The thermal conductor is graphene, boron nitride and aluminum oxide in a weight ratio of 1:3:4.

[0025] Preparation Example 3 The difference between this preparation example and preparation example 2 is that the preparation method of the thermal conductor-halloysite nanotube composite material in this preparation example comprises the following steps: A1, adding the halloysite nanotubes to a 3 mol / L hydrochloric acid solution, heating and stirring for 7 h in a water bath, centrifuging to separate the solid matter, and washing and grinding the solid matter to obtain the halloysite nanotubes after hydrochloric acid etching; A2, mixing the hydrochloric acid-etched halloysite nanotubes obtained in step A1, a thermal conductor and water, and performing ultrasonic dispersion for 50 minutes in an ice bath, and then vacuum drying the obtained suspension; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 28 hours, and grind into powder to obtain the thermal conductor-halloysite nanotube composite material.

[0026] In step A2, the weight ratio of the halloysite nanotubes, the thermal conductor and the water after the hydrochloric acid etching is 1:11:90; The thermal conductor is graphene, boron nitride and aluminum oxide in a weight ratio of 1:4:5.

[0027] Preparation Example 4 The difference between this preparation example and preparation example 2 is that the preparation method of the thermal conductor-halloysite nanotube composite material in this preparation example comprises the following steps: A1, adding the halloysite nanotubes to a 3 mol / L hydrochloric acid solution, heating and stirring for 6 h in a water bath, centrifuging to separate the solid matter, and washing and grinding the solid matter to obtain the halloysite nanotubes after hydrochloric acid etching; A2, mixing the hydrochloric acid-etched halloysite nanotubes obtained in step A1, a thermal conductor and water, and performing ultrasonic dispersion for 40 minutes in an ice bath, and then vacuum drying the obtained suspension; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 30 hours, and grind into powder to obtain the thermal conductor-halloysite nanotube composite material.

[0028] In step A2, the weight ratio of the halloysite nanotubes, the thermal conductor and water after hydrochloric acid etching is 1:13:100; the thermal conductor is graphene, boron nitride and aluminum oxide in a weight ratio of 1:5:6.

[0029] Example 1 The present embodiment provides a recycled concrete with high thermal conductivity, which includes the following raw materials in parts by weight: 120 parts of cement, 15 parts of mineral powder, 20 parts of fly ash, 150 parts of coarse aggregate, 320 parts of fine aggregate, 14 parts of thermal conductor-halloysite nanotube composite material, 7 parts of modified polyacrylonitrile-based carbon fiber, 40 parts of water, and 5 parts of admixture.

[0030] The method for preparing the recycled concrete with high thermal conductivity in this preparation example comprises the following steps: S1. Mix cement, mineral powder, fly ash, coarse aggregate and fine aggregate at 32 rpm for 12 min; S2, adding the thermal conductor-halloysite nanotube composite material, modified polyacrylonitrile-based carbon fiber and 50% of water, and mixing and stirring at 320 rpm for 6 minutes; S3. Add the admixture and the remaining water, mix and stir at 430 rpm for 114 minutes to obtain the recycled concrete with high thermal conductivity.

[0031] The modified polyacrylonitrile-based carbon fiber used in this embodiment is prepared by Preparation Example 1, the thermal conductor-halloysite nanotube composite material is prepared by Preparation Example 2, and the admixtures are polycarboxylic acid high-efficiency water reducer, air entraining agent and dispersant in a weight ratio of 5:2:3.

[0032] Embodiment 2-4 Example 2 The difference between this embodiment and Embodiment 1 is that, when preparing recycled concrete with high thermal conductivity, the total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 21 parts, and the weight ratio of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 1.6:1.

[0033] Example 3 The difference between this embodiment and Embodiment 1 is that, when preparing recycled concrete with high thermal conductivity, the total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 21 parts, and the weight ratio of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 1.8:1.

[0034] Example 4 The difference between this embodiment and Embodiment 1 is that, when preparing recycled concrete with high thermal conductivity, the total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 21 parts, and the weight ratio of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 2.4:1.

[0035] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that no modified polyacrylonitrile-based carbon fiber is added when preparing the recycled concrete with high thermal conductivity.

[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing the recycled concrete with high thermal conductivity, no thermal conductive agent-halloysite nanotube composite material is added.

[0037] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the recycled concrete with high thermal conductivity, the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber are not added.

[0038] Experimental testing: The concrete was prepared into a concrete panel (length×width×height=300mm×300mm×50mm), which was cured at a temperature of 30°C and a humidity of 60%. After 28 days, the thermal conductivity and mechanical properties of the concrete panel were tested, wherein the test standard for thermal conductivity was GB / T 10294, and the test standard for compressive strength and flexural strength was GB / T50081.

[0039] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0040] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Result analysis: The difference between Examples 2-4 and Example 1 is that when preparing recycled concrete with high thermal conductivity, the total weight of the thermal conductor-halloysite nanotube composite material and modified polyacrylonitrile-based carbon fiber is 21 parts, and the weight ratio of the thermal conductor-halloysite nanotube composite material and modified polyacrylonitrile-based carbon fiber is different. Combined with the experimental test results of Table 1, it can be seen that when the weight ratio of the thermal conductor-halloysite nanotube composite material and modified polyacrylonitrile-based carbon fiber is 2:1, the obtained recycled concrete with high thermal conductivity has high compressive strength and flexural strength, and has higher thermal conductivity. The difference between Comparative Example 1 and Example 1 is that when preparing recycled concrete with high thermal conductivity, modified polyacrylonitrile-based carbon fiber is not added. The difference between Comparative Example 2 and Example 1 is that when preparing recycled concrete with high thermal conductivity, no thermal conductor-halloysite nanotube composite material is added. The difference between Comparative Example 3 and Example 1 is that when preparing recycled concrete with high thermal conductivity, no thermal conductor-halloysite nanotube composite material and modified polyacrylonitrile-based carbon fiber are added. Combined with the experimental test results in Table 1, it can be seen that when preparing high-conductivity When preparing recycled concrete with high thermal conductivity, the combination of thermal conductor-halloysite nanotube composite material and modified polyacrylonitrile-based carbon fiber can effectively improve the thermal conductivity and mechanical strength of the recycled concrete with high thermal conductivity.

[0041] Embodiment 5-6 The difference between Example 5-6 and Example 1 is that the weight fractions of some components are changed when preparing the recycled concrete with high thermal conductivity. See Table 2 for the differences.

[0042] Table 2 - Differences between Examples 5-6 and Example 1 Ingredients (parts by weight) Example 1 Example 5 Example 6 cement 120 138 150 Mineral powder 15 22 30 Fly ash 20 26 30 coarse aggregate 150 190 210 fine aggregate 320 350 400 Thermal Conductor-Halloysite Nanotube Composite Material 14 14 14 Modified polyacrylonitrile-based carbon fiber 7 7 7 water 40 50 55 Admixtures 5 8 10 The experimental test results of Examples 5-6 are shown in Table 3.

[0043] Table 3 - Experimental test results of Examples 5-6 Result analysis: The difference between Examples 5-6 and Example 1 is that when preparing recycled concrete with high thermal conductivity, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that when preparing recycled concrete with high thermal conductivity, the recycled concrete with high thermal conductivity prepared in Example 5 has better comprehensive performance.

[0044] Embodiment 7-9 The difference between Examples 7-9 and Example 5 is that when preparing recycled concrete with high thermal conductivity, on the premise that the weight ratio of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 2:1, the proportion of the total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber in the total weight of the recycled concrete raw materials with high thermal conductivity is changed, and a better weight proportion is selected.

[0045] In Example 5, the total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber is 21 parts, and the total weight of the recycled concrete with high thermal conductivity is 805 parts.

[0046] Therefore, it is not difficult to conclude that in Example 5, the sum of the weights of the thermal conductor-halloysite nanotube composite material (referred to as variable 1) and the modified polyacrylonitrile-based carbon fiber (referred to as variable 2) accounts for 2.6% of the total weight of the raw materials of the recycled concrete with high thermal conductivity (referred to as the matrix).

[0047] The differences between Examples 7-9 and Example 5 are shown in Table 4.

[0048] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.

[0049] Table 4 - Differences between Examples 7-9 and Example 5 The experimental test results of Examples 7-9 are shown in Table 5.

[0050] Table 5 - Experimental test results of Examples 7-9 Result analysis: The difference between Examples 7-9 and Example 5 is that when preparing recycled concrete with high thermal conductivity, when the proportion of the thermal conductor-halloysite nanotube composite material (referred to as variable 1) and the modified polyacrylonitrile-based carbon fiber (referred to as variable 2) in the recycled concrete with high thermal conductivity (referred to as the matrix) is between 2.2-3.3%, the thermal conductivity and mechanical strength of the recycled concrete with high thermal conductivity obtained are better. When the proportion of the thermal conductor-halloysite nanotube composite material (referred to as variable 1) and the modified polyacrylonitrile-based carbon fiber (referred to as variable 2) in the recycled concrete with high thermal conductivity (referred to as the matrix) is 2.6%, the thermal conductivity and mechanical strength of the recycled concrete with high thermal conductivity obtained are better.

[0051] Embodiment 10-11 Example 10 The difference between this embodiment and embodiment 5 is that when preparing recycled concrete with high thermal conductivity, different preparation parameters of the thermal conductor-halloysite nanotube composite material are used. The thermal conductor-halloysite nanotube composite material in this embodiment is prepared by Preparation Example 3.

[0052] Embodiment 11 The difference between this embodiment and embodiment 5 is that when preparing recycled concrete with high thermal conductivity, different preparation parameters of the thermal conductor-halloysite nanotube composite material are used. The thermal conductor-halloysite nanotube composite material in this embodiment is prepared by Preparation Example 4.

[0053] The experimental test results of Examples 10-11 are shown in Table 6.

[0054] Table 6 - Experimental test results of Examples 10-11 Result analysis: The difference between Examples 10-11 and Example 5 is that, when preparing recycled concrete with high thermal conductivity, the thermal conductor-halloysite nanotube composite material prepared by Preparation Example 3 can better improve the thermal conductivity and mechanical strength of the recycled concrete with high thermal conductivity.

[0055] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A recycled concrete with high thermal conductivity, characterized in that: The invention comprises the following raw materials in parts by weight: 120-150 parts of cement, 15-30 parts of mineral powder, 20-30 parts of fly ash, 150-210 parts of coarse aggregate, 320-400 parts of fine aggregate, 10-18 parts of thermal conductor-halloysite nanotube composite material, 5-9 parts of modified polyacrylonitrile-based carbon fiber, 40-55 parts of water and 5-10 parts of admixture.

2. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The preparation method of the thermal conductor-halloysite nanotube composite material comprises the following steps: A1, adding the halloysite nanotubes to a 3 mol / L hydrochloric acid solution, heating and stirring in a water bath for 6-8 hours, centrifuging to separate the solid matter, and washing and grinding the solid matter to obtain the halloysite nanotubes after hydrochloric acid etching; A2, mixing the hydrochloric acid-etched halloysite nanotubes obtained in step A1, a thermal conductor and water, and ultrasonically dispersing them in an ice bath for 40-60 minutes, and then vacuum drying the obtained suspension; A3. After vacuum drying, centrifuge to separate the solid phase, wash the solid phase, vacuum dry for 24-30 hours, and grind into powder to obtain the thermal conductor-halloysite nanotube composite material.

3. The recycled concrete with high thermal conductivity according to claim 2, characterized in that: In the step A2, the weight ratio of the halloysite nanotubes, the thermal conductor and the water after the hydrochloric acid etching is 1:(9-13):(80-100).

4. The recycled concrete with high thermal conductivity according to claim 2, characterized in that: The thermal conductor includes graphene, boron nitride and aluminum oxide in a weight ratio of 1:(3-5):(4-6).

5. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The preparation method of the modified polyacrylonitrile-based carbon fiber comprises the following steps: dissolving dopamine hydrochloride in a Tris aqueous solution, adding the polyacrylonitrile-based carbon fiber and soaking for 10-12 hours, washing, and freeze-drying to obtain the modified polyacrylonitrile-based carbon fiber; the dosage ratio of dopamine hydrochloride to the Tris aqueous solution is (4-6) mg: 1 mL.

6. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The weight ratio of the thermal conductor-halloysite nanotube composite material to the modified polyacrylonitrile-based carbon fiber is (1.6-2.4):

1.

7. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The total weight of the thermal conductor-halloysite nanotube composite material and the modified polyacrylonitrile-based carbon fiber accounts for 2.2-3.3% of the total weight of the raw materials of the recycled concrete with high thermal conductivity.

8. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The coarse aggregate consists of natural coarse aggregate and recycled coarse aggregate in a weight ratio of (2.5-4):

1.

9. The recycled concrete with high thermal conductivity according to claim 1, characterized in that: The admixture includes a polycarboxylic acid high-efficiency water reducer, an air entraining agent and a dispersant in a weight ratio of (4-6): (2-3): (2-3).

10. A method for preparing recycled concrete with high thermal conductivity according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix cement, mineral powder, fly ash, coarse aggregate and fine aggregate at 300-350 rpm for 10-15 min; S2, adding the thermal conductor-halloysite nanotube composite material, modified polyacrylonitrile-based carbon fiber and 50% of water, and mixing and stirring at 300-350 rpm for 5-8 minutes; S3. Add the admixture and the remaining water, mix and stir at 400-450 rpm for 10-15 minutes to obtain the recycled concrete with high thermal conductivity.

Citation Information

Cited By

  • High-heat-transfer cement-based material and preparation method thereof

    CN120647274A